Water soluble polymer binder containing aromatic compound in anode materials of secondary battery

KR103019788B1Active Publication Date: 2026-09-16MIWON COMML
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020230067205
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-05-24
Publication Date
2026-09-16
Estimated Expiration
2043-05-24

Smart Images

  • Figure 112023057799938-PAT00004_ABST
    Figure 112023057799938-PAT00004_ABST
Patent Text Reader

Abstract

The present invention relates to a binder for electrodes of a secondary battery prepared by polymerizing a composition comprising at least two types of water-soluble monomers and at least one type of fat-soluble monomer. The binder of the present invention achieves high adhesion compared to conventional SBR / CMC binders, allowing high adhesion to be confirmed even after rolling, and can efficiently control the volume expansion of silicon, thereby contributing to an increase in the cell capacity of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a polymer water-soluble binder comprising an aromatic compound. Background Technology

[0003] Lithium-ion batteries are widely used in the electrical, electronic, telecommunications, and computer industries, ranging from small-capacity home appliances to high-capacity batteries used in electric and hybrid vehicles and energy storage systems (ESS), and their application fields are gradually expanding.

[0004] With the expansion of application fields, the need for secondary batteries capable of high energy density, safety, fast charging, and long lifespan is becoming prominent.

[0005] Conventional typical lithium secondary batteries use graphite as the negative electrode active material, and charging and discharging proceed as lithium ions from the positive electrode are repeatedly inserted into and extracted from the negative electrode.

[0006] Although the theoretical capacity of the battery varies depending on the type of electrode active material, generally, a problem arises where the charge and discharge capacities decrease as the cycle progresses.

[0007] The primary cause of this phenomenon is that the active materials become separated from each other or between the active materials and the current collector due to changes in electrode volume that occur as the battery charges and discharges, thereby preventing the active materials from performing their functions.

[0008] Recently, silicon with a high discharge capacity is sometimes used in combination with graphite to increase discharge capacity; however, since silicon undergoes significant volume changes during the insertion and extraction of lithium ions, the volume expansion of the material increases significantly as charging and discharging proceeds. This leads to the detachment of the anode material from the electrode material, causing a problem in which the battery capacity rapidly decreases during repeated cycles.

[0009] Therefore, there is an urgent need for research on binders and electrode materials that can prevent separation between electrode active materials or between electrode active materials and current collectors through strong adhesion, and control the volume expansion of electrode active materials that occurs during repeated charging and discharging, thereby promoting structural stability of the electrode and consequently improving battery performance.

[0010] The binder is primarily used to secure adhesion or binding force between the electrode active material and the electrode current collector, and also serves as a buffer against the expansion and contraction of the active material due to the insertion and extraction of lithium ions.

[0011] As the existing solvent-based binder polyvinylidene fluoride (PVdF) fails to meet the above requirements, a method has recently been proposed to produce emulsion particles by polymerizing styrene-butadiene rubber (SBR) in the aqueous phase and mixing them with neutralizing agents, which is currently being used commercially.

[0012] These binders have the advantage of being environmentally friendly and capable of increasing battery capacity even with the use of less binder. However, even in this case, while adhesion persistence is improved due to rubber elasticity, it does not provide a significant effect on the adhesive strength itself.

[0013] Therefore, there is a high need to develop a binder that can withstand silicon expansion, does not decompose during battery charging and discharging to ensure the structural stability of the electrode, and has excellent adhesive strength. Prior art literature

[0015] Registered Patent 10-2164435 Published Patent 10-2018-0109740 Published Patent 10-2018-0099561 Published Patent 10-2020-0133699 The problem to be solved

[0016] Although graphite is used in the negative electrodes of existing secondary batteries, its capacity is insufficient, which limits its application in electric vehicles or ESS that require high capacity.

[0017] Although high-capacity silicon materials are gaining attention as a replacement for graphite, silicon materials undergo significant volume changes during the insertion and extraction of lithium ions, leading to a phenomenon that degrades the battery's lifespan characteristics.

[0018] Since the adhesive strength of conventionally used SBR / CMC is insufficient to effectively control the volume expansion of silicone materials, there is a need for a high-adhesion binder.

[0019] The purpose is to improve the adhesion of the binder currently used for secondary battery negative electrodes and, consequently, to improve the lifespan of secondary batteries using silicon materials for the negative electrode.

[0020] In secondary batteries, silicon materials offer high capacity but suffer from the disadvantage of severe volume expansion, which leads to a degradation in lifespan characteristics. To address this, there is a need for a binder with strong adhesive properties that exhibits high resistance to silicon volume expansion. While conventional water-soluble binders utilize only water-soluble monomers, the present invention is characterized by the introduction of an emulsifier into a water-soluble binder to mix in a lipid-soluble monomer, thereby producing a water-soluble polymer.

[0021] Generally, when using lipid-soluble monomers, phase separation occurs, forming water-soluble and lipid-soluble polymers separately; the water-soluble polymer exists in a liquid phase dissolved in water, while the lipid-soluble monomer exists in a solid phase polymerized. However, by using an emulsifier, the lipid-soluble monomer emulsified in the droplet is transferred through the principle of emulsion polymerization, and at an appropriate concentration, a liquid-phase water-soluble polymer with a single phase is formed. Through this process, water-soluble binders containing various lipid-soluble monomers can be synthesized, and in particular, monomers having an aromatic compound structure can be synthesized together. This allows for the improvement of the adhesion of binders for secondary battery anodes. means of solving the problem

[0023] In one embodiment of the present invention, the binder for the electrode of the secondary battery of the present invention is a compound satisfying the following chemical formula 1, and can be prepared by polymerizing a composition comprising at least two water-soluble monomers and at least one fat-soluble monomer.

[0025] [Chemical Formula 1]

[0026]

[0027] Specifically, in the above chemical formula 1, k can have a range of 500 to 950, l can have a range of 50 to 500, and m can have a range of 1 to 200.

[0028] In the above chemical formula 1, M may be one selected from alkali metals, alkaline earth metals, transition metals, and nitrogen compounds having a cation form.

[0029] R in Chemical Formula 1 above 1 It can be a molecule having 1 to 5 benzene rings.

[0030] In one embodiment of the present invention, the binder for the electrode of the secondary battery of the present invention comprises, as the water-soluble monomer, anionic unsaturated monomers such as vinylpyrrolidone, silica, 4-vinylphenol, phosphoric acid, 4-vinylphenyl sulfate, maleic acid, diallyldimethylammonium chloride, (meth)acrylic acid, (anhydrous)maleic acid, itaconic acid, cinnamic acid, vinylsulfonic acid, allyltoluenesulfonic acid, vinyltoluenesulfonic acid, styrenesulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, 2-(meth)acryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, 2-hydroxyethyl methacrylic acid, 2-hydroxyethyl(meth)acryloylphosphate, and salts thereof, mercapto group-containing unsaturated monomers, and phenolic hydroxyl groups It may include one or more selected from the group consisting of: (meth)acrylamide, N-ethyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, etc., unsaturated monomers containing amide groups; N,N-dimethylaminoethyl(meth)acrylate, N,N-dimethylaminopropyl(meth)acrylate, and N,N-dimethylaminopropyl(meth)acrylamide.

[0031] In one embodiment of the present invention, the binder for the electrode of the secondary battery of the present invention is, as the lipid-soluble monomer, an aromatic vinyl compound such as styrene, vinyltoluene, α-methylstyrene, or divinylbenzene, methyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, isobutyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, benzyl (meth)acrylate, mono or di(meth)acrylate of (poly)ethylene glycol, mono or di(meth)acrylate of (poly)propyl glycol, mono- or di-(meth)acrylate of 1,4-butanediol, mono- or di- of trimethylolpropane It may include one or more selected from unsaturated carboxylic acid esters such as tri-(meth)acrylates, allyl compounds such as diallyl phthalate, diallyl acrylamide, trialyl(iso)cyanurate, and trialyl trimellitate, (poly)oxyalkylene glycol di(meth)acrylates such as (poly)ethylene glycol di(meth)acrylate and (poly)propylene glycol di(meth)acrylate, butadiene, isoprene, and chloroprene.

[0032] In one embodiment of the present invention, M in Formula 1 of the binder for the electrode of the secondary battery of the present invention may include one or more selected from lithium, sodium, potassium, rubidium, magnesium, calcium, barium, titanium, zirconium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, manganese, iron, cobalt, nickel, palladium, platinum, copper, silver, gold, zinc, cadmium, mercury, and ammonium ions.

[0033] In one embodiment of the present invention, the initiator of the binder for the electrode of the secondary battery of the present invention may comprise one or more selected from persulfates such as benzoin derivatives, benzyl derivatives, acetophenone derivatives, benzophenone derivatives, sodium persulfate, potassium persulfate, and ammonium persulfate; hydrogen peroxide, t-butyl peroxide, methyl ethyl ketone peroxide, 2,2'-azobis(2-amidinopropane)dihydrochloride, 2,2'-azobis[2-(2-imidazoline-2-yl)propane]dihydrochloride, and compounds in which a reducing compound such as L-ascorbic acid or sodium bisulfite is combined with a persulfate or peroxide.

[0034] In one embodiment of the present invention, the emulsifier of the binder for the electrode of the secondary battery of the present invention may include one or more selected from polyoxyalkylenealkylphenyl ether, polyoxyalkylenealkyl ether, alkyl polyglucoside, polyglycerin alkyl ether, polyglycerin fatty acid ester, polyoxyalkylene fatty acid ester, sorbitan fatty acid ester, fatty acid soap, rosin soap, alkyl sulfonate, alkylaryl sulfonate, alkyl sulfosuccinate, polyoxyethylene alkyl sulfate, polyoxyethylenearyl sulfate, sodium lauryl sulfate, stearyl trimethylammonium, cetyl trimethylammonium, and lauryl trimethylammonium.

[0035] In one embodiment of the present invention, the molecular weight (Mw) of the binder for the electrode of the secondary battery of the present invention may be 200,000 to 2,000,000.

[0036] Specifically, the present invention manufactures a binder by synthesizing a water-soluble binder with a rigid structure of high adhesion by adding a lipid-soluble monomer through an emulsifier, and initiating a chain reaction of polymer polymerization through an initiator, in particular by having an aromatic compound within the structure of the polymer, thereby enabling the control of silicon volume expansion when applied to a secondary battery. Effects of the invention

[0038] The binder of the present invention achieves higher adhesion compared to conventional SBR / CMC binders, and high adhesion can be confirmed even after rolling. Through this, the volume expansion of silicon can be efficiently controlled, which can contribute to an increase in the cell capacity of secondary batteries. Brief explanation of the drawing

[0040] Figure 1 is a graph showing the results of an adhesion test conducted before rolling using electrodes made by the methods of Examples 1 to 3, Comparative Examples 1 to 3, and Reference Example 1. Figure 2 is a graph showing the results of an adhesion test conducted after rolling with electrodes made by the methods of Examples 1 to 3, Comparative Examples 1 to 3, and Reference Example 1. Specific details for implementing the invention

[0041] The binder for the electrode of the secondary battery according to the present invention is a compound satisfying the following chemical formula 1, and is prepared by polymerizing a composition comprising at least two water-soluble monomers and at least one lipid-soluble monomer.

[0043] [Chemical Formula 1]

[0044]

[0045] In addition to the specific monomers listed below, water-soluble monomers with similar functions may generally be used. Specifically, anionic unsaturated monomers and their salts, mercapto group-containing unsaturated monomers, phenolic hydroxyl group-containing unsaturated monomers, such as vinylpyrrolidone, silica, 4-vinylphenol, phosphoric acid, 4-vinylphenyl sulfate, maleic acid, diallyldimethylammonium chloride, (meth)acrylic acid, (anhydrous)maleic acid, itaconic acid, cinnamic acid, vinylsulfonic acid, allyltoluenesulfonic acid, vinyltoluenesulfonic acid, styrenesulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, 2-hydroxyethyl methacrylic acid, and 2-hydroxyethyl(meth)acryloylphosphate; Unsaturated monomers containing amide groups such as (meth)acrylamide, N-ethyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide; and one or more selected from the group consisting of N,N-dimethylaminoethyl(meth)acrylate, N,N-dimethylaminopropyl(meth)acrylate, and N,N-dimethylaminopropyl(meth)acrylamide.

[0046] In addition to the specific monomers listed below, any lipid-soluble monomers with similar functions may be used. Aromatic vinyl compounds such as styrene, vinyltoluene, α-methylstyrene, and divinylbenzene; unsaturated carboxylic acid esters such as (meth)acrylate, 2-hydroxyethyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, isobutyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, and benzyl (meth)acrylate; mono- or di(meth)acrylate of (poly)ethylene glycol; mono- or di(meth)acrylate of (poly)propyl glycol; mono- or di-(meth)acrylate of 1,4-butanediol; mono-, di- or tri-(meth)acrylate of trimethylolpropane; and diallyl phthalate, It includes one or more selected from the group consisting of allyl compounds such as diallylacrylamide, trialyl(iso)cyanurate, and trialyltrimellitate; (poly)oxyalkylene glycol di(meth)acrylates such as (poly)ethylene glycol di(meth)acrylate and (poly)propylene glycol di(meth)acrylate; butadiene; isoprene; and chloroprene.

[0047] Among lipid-soluble monomers, those having the structure of aromatic compounds exhibit strong rolling resistance, which helps improve the rigid properties of water-soluble binders.

[0048] In solution polymerization, when polymerizing lipid-soluble monomers and water-soluble monomers, phase separation occurs, causing droplet separation; consequently, the lipid-soluble and water-soluble monomers tend to separate and form separately within the reactor. Therefore, a binder is synthesized using a reactive emulsifier in which the water-soluble and lipid-soluble monomers are mixed within the polymer. R of the synthesized binder 1 It is a molecule in the form of having 1 to 5 benzene rings.

[0049] Reactive emulsifiers have ionic hydrophilic groups as functional groups, such as anionic hydrophilic groups or cationic hydrophilic groups. Anionic hydrophilic groups include -SO2M, -R1-SO3M, R2-COOM, -PO3M2, PO3MH, or -COOR3-COOM functional groups (wherein M is a hydrogen atom, an alkali metal atom such as lithium, sodium, potassium, or an ammonium salt), and cationic hydrophilic groups include alkylamines, ethoxylate amine derivatives, alkylimidazoline derivatives, or quaternary ammonium halide functional groups.

[0050] Anionic reactive emulsifiers are anionic types having polymerizable unsaturated bonds, and in addition to having double bonds, alkyl groups, aromatic compounds, and anionic groups, they have ether groups, ester groups, sulfonate groups, sulfoxide groups, sulfide groups, hydroxyl groups, etc. The above anionic groups consist of sulfonic acid groups, carboxylic acid groups, phosphate groups, sulfate groups, or salts thereof.

[0051] Specific examples of anionic reactive emulsifiers include one or more selected from the group consisting of polyoxyalkylene-1-(aryloxymethyl)alkyl ether sulfate esters and their salts, polyoxyalkylene-1-(aryloxymethyl)alkyl ether phosphate esters and their salts, polyoxyalkylene-1-alkoxymethyl-2-(2-propenoxy)ethyl ether sulfate esters and their salts, and polyoxyalkylene-1-alkoxymethyl-2-(2-propenoxy)ethyl ether phosphate esters and their salts.

[0052] Cationic reactive emulsifiers may include cationic compounds having polymerizable unsaturated bonds, double bonds, and cationic groups, as well as alkyl and aromatic compounds, and may simultaneously have functional groups such as ether groups, ester groups, sulfonate groups, sulfoxide groups, sulfide groups, and hydroxyl groups.

[0053] Specific examples of cationic reactive emulsifiers include one or more selected from the group consisting of cetrimonium, stearalkonium chloride, benzalkonium chloride, propyltrimonium chloride, lauryl betaine, hexamethyldisiloxane, and their salts.

[0054] The emulsifier used to prepare the binder of Formula 1 above preferably comprises one or more selected from polyoxyalkylenealkylphenyl ether, polyoxyalkylenealkyl ether, alkyl polyglucoside, polyglycerin alkyl ether, polyglycerin fatty acid ester, polyoxyalkylene fatty acid ester, sorbitan fatty acid ester, fatty acid soap, rosin soap, alkyl sulfonate, alkylaryl sulfonate, alkyl sulfosuccinate, polyoxyethylene alkyl sulfate, polyoxyethylenearyl sulfate, stearyl trimethylammonium, cetyl trimethylammonium, and lauryl trimethylammonium.

[0055] An initiator is a substance that receives energy to form radicals and initiates a chain reaction of polymer polymerization; in the present invention, it is not significantly limited by the polymerization method. The initiator is appropriately determined according to the polymerization type, and photodegradable polymerization initiators, thermal degradable polymerization initiators, redox polymerization initiators, etc., may be used, and their use is not particularly limited.

[0056] Photodegradable polymerization initiators include benzoin derivatives, benzyl derivatives, acetophenone derivatives, benzophenone derivatives, and azo compounds; thermal degradable polymerization initiators include persulfates such as sodium persulfate, potassium persulfate, and ammonium persulfate; peroxides such as hydrogen peroxide, t-butyl peroxide, and methyl ethyl ketone peroxide; and azo compounds such as 2,2'-azobis(2-amidinopropane)dihydrochloride and 2,2'-azobis[2-(2-imidazoline-2-yl)propane]dihydrochloride; and redox polymerization initiators may also be used in combination with persulfates or peroxides, such as reducing compounds like L-ascorbic acid or sodium bisulfite.

[0057] In Chemical Formula 1, M is one selected from alkali metals, alkaline earth metals, transition metals, and nitrogen compounds having the form of a cation. Specifically, M includes one or more selected from lithium, sodium, potassium, rubidium, magnesium, calcium, barium, titanium, zirconium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, manganese, iron, cobalt, nickel, palladium, platinum, copper, silver, gold, zinc, cadmium, mercury, and ammonium ions.

[0058] If hydrogen ions remain at the position of M, hydrogen gas may be generated within the battery, and if the generated gas is ignited by overheating or a spark inside the battery, there may be a risk of explosion and fire, which reduces the safety of the battery. To prevent this problem, the hydrogen ions are replaced and bonded with one selected from alkali metals, alkaline earth metals, transition metals, and nitrogen compounds that have a positive ion form.

[0059] In the above chemical formula 1, k has a range of 500 to 950, l has a range of 50 to 500, and m has a range of 1 to 200, and the meaning is as described below.

[0060] The range of the value corresponding to k in Chemical Formula 1 above must be maintained between 500 and 950 to effectively control volume expansion and increase adhesion. If the k value is less than 500, sufficient adhesion cannot be secured, which prevents the control of volume expansion of the silicon anode material and fails to properly exhibit physical properties as a binder. On the other hand, if the k value exceeds 950, dispersion stability decreases, and consequently, flexibility cannot be secured during the electrode manufacturing process, which may lead to a problem where cracks form in the electrode.

[0061] The range of the value corresponding to l in Chemical Formula 1 above must be maintained between 50 and 500, which is related to the stability of the slurry. If the value of l is less than 50, the stability of the slurry decreases, which may result in a problem where the coating is not uniform. If the value of l exceeds 500, the stability of the slurry may improve, but it may cause hydrogen gas to be generated within the battery. Hydrogen gas is generated by remaining hydrogen ions and can reduce the stability of the battery. This is because if hydrogen gas is generated, it may be ignited by overheating or sparks inside, posing a risk of explosion and fire.

[0062] The range of the value corresponding to m in Chemical Formula 1 above must be maintained between 1 and 200, which is related to adhesion and impact resistance. If the range is exceeded, problems may arise such as separation of the organic phase or insufficient inhibition of silicone expansion.

[0063] The binder produced according to the present invention preferably has a molecular weight of 200,000 to 2,000,000. Molecular weight is related to adhesion, and generally, as the molecular weight increases, adhesion increases, enabling good electrode performance. However, if the molecular weight exceeds 2,000,000, the viscosity of the binder increases, which causes problems such as reduced solubility during the battery manufacturing process. If the molecular weight becomes less than 200,000, the viscosity of the binder decreases, and the adhesion to the electrode decreases, making it unable to withstand volume changes of the negative electrode material and thus unsuitable for use.

[0064] The adhesive strength of the binder can be evaluated by manufacturing electrodes, and electrode adhesion is one of the important factors determining the lifespan characteristics of the battery. Stronger adhesion prevents the active material from detaching from the copper electrode and controls silicon expansion, thereby improving lifespan characteristics.

[0065] The binder produced according to the present invention is manufactured by synthesizing water-soluble monomers and oil-soluble monomers with the addition of an emulsifier, thereby possessing benzene rings within the polymer structure. Due to its strong adhesive force, it forms a strong bond with copper, firmly holding the active material; consequently, it controls the volume expansion of silicon-based anodes, which can lead to improved lifespan characteristics. Furthermore, while polymer binders with rigid properties often lose their adhesive strength due to structural collapse after rolling, the binder produced according to the present invention features an aromatic compound structure within the polymer that provides free volume and enhances impact resistance. Consequently, the structure does not collapse even after rolling, allowing it to exhibit strong bonding strength.

[0066] In addition, as the thickness of the electrode increases, the volume of the electrode that the binder can hold increases, so the adhesive strength tends to decrease; however, in the case of the binder manufactured according to the present invention, it was confirmed that it has strong bonding strength even when the thickness of the electrode is increased by utilizing this characteristic.

[0068] Manufacture of binders

[0069] <Example 1>

[0070] 1. 300g of water is placed in a reactor equipped with a condenser and a thermometer, nitrogen is filled for 1 hour, and then the temperature is raised to 80℃ while stirring.

[0071] 2. Prepare a total of 50g of acrylamide, acrylic acid, and the lipid-soluble monomer styrene (an aromatic compound) in a molar ratio of 70:25:5, and 2g of sodium lauryl sulfate, and dissolve them in 75g of water to prepare a monomer mixture. Prepare an initiator mixture by dissolving 0.2g of 2,2'-azobis(2-amidinopropane)dihydrochloride in 75g of water.

[0072] 3. Add the initiator mixture to the prepared monomer mixture dropwise into the reactor for 2 hours while stirring. After sufficient aging following the addition, salt treatment is performed using sodium hydroxide at 60°C for at least 4 hours to adjust the pH to 7~8.

[0074] <Example 2>

[0075] Except for using phenoxybenzyl acrylate as the lipid-soluble monomer, the experiment was conducted in the same manner as Example 1 and designated as Example 2.

[0077] <Example 3>

[0078] The experiment was conducted in the same manner as Example 1, except that 2-phenyl-2-phenoxyethyl acrylate was used as the lipid-soluble monomer, and this was designated as Example 3.

[0080] <Comparative Example 1>

[0081] The experiment was conducted in the same manner as Example 1, except that acrylamide and acrylic acid were used in a molar ratio of 70:30 and no lipid-soluble monomer was used, and this was designated as Comparative Example 1.

[0083] <Comparative Example 2>

[0084] The experiment was conducted in the same manner as Example 1, except that a long chain Lauryl Methacrylate monomer was used instead of a lipid-soluble monomer, and this was designated as Comparative Example 2.

[0086] <Comparative Example 3>

[0087] The experiment was conducted in the same manner as Example 1, except that polypropylene glycol monomethacrylate having a ring was used instead of a lipid-soluble monomer, and this was designated as Comparative Example 3.

[0089] <Reference Example 1>

[0090] Commercially available SBR (Styrene Butadiene Rubber) / CMC is used in a molar ratio of SBR:CMC = 1:1 and is designated as Reference Example 1.

[0092] Electrode slurry manufacturing

[0093] A cathode material (artificial graphite:SiO=8:2), a conductive material, and a binder prepared above are mixed in a molar ratio of 96.3:1.0:2.7, and a slurry is prepared by stirring at 5000 RPM for 1 hour using a homomixer.

[0095] Electrode manufacturing

[0096] After uniformly applying a slurry onto copper using a doctor blade, the slurry is dried in an 80°C convection oven for 1 hour, and then rolled to 90% of the electrode thickness. After rolling, the electrode is dried by vacuum drying at 100°C for 10 hours to obtain the electrode.

[0098] Adhesion test

[0099] <Experimental Example 1>

[0100] The adhesion strength between the cathode slurry and the current collector when the binders specified in Examples 1 to 3, Comparative Examples 1 to 3 and Reference Examples were used was measured using a tensile testing machine (Universal Testing Machine, model name zwickLine Z1.0TH).

[0101] The electrodes prepared according to Examples 1 to 3, Comparative Examples 1 to 3, and Reference Example 1 are cut to a width of 2.0 cm and attached to a slide glass using double-sided tape. The force is measured when a length of 50 mm of the negative active material layer is detached from the negative current collector at a speed of 100 mm / min and an angle of 180 degrees.

[0102] The averaged force values ​​from a measurement distance of 10 mm to 80 mm are shown in Table 1 below.

[0104] bookbinder Press total thickness (μm) Pre-rolling adhesion (gf / 2cm) 90% Rolled Adhesion (gf / 2cm) Example 1 Manufactured using acrylamide, acrylic acid, and styrene 62 233 262 Example 2 Manufactured using acrylamide, acrylic acid, and phenoxybenzyl acrylate 62 175 217 Example 3 Prepared using acrylamide, acrylic acid, and 2-phenyl-2-phenoxyethylacrylate 62 222 258 Comparative Example 1 Manufactured using acrylamide and acrylic acid 66 185 85 Comparative Example 2 Manufactured using acrylamide, acrylic acid, and lauryl methacrylate 60 147 94 Comparative Example 3 Manufactured using acrylamide, acrylic acid, and propylene glycol monomethacrylate 59 205 107 Reference Example 1 Use commercially available SBR / CMC 56 99 139

[0105] Rolling is a process that reduces the thickness of coated electrodes and increases energy density by applying pressure with rolls. By applying pressure, it homogenizes the thickness of the electrode composite layer (active material + conductive material + binder), improves the bonding strength between the composite layer and the current collector, enhances the bonding strength between active material particles, and imparts smooth mobility to ions, ultimately increasing the energy density of the electrode.

[0106] Figures 1 and 2 respectively show graphs of the results of adhesion tests conducted before rolling and after rolling using electrodes made by the methods of Examples 1 to 3, Comparative Examples 1 to 3, and Reference Example 1.

[0107] Example 1 is a binder structure incorporating styrene monomer, and the adhesive strength increased by 12% from 233 to 262 after rolling. As can be seen in FIG. 1, the adhesive strength test values ​​before rolling from a measurement distance of 10 mm to 80 mm are approximately 132 to 406 gf / 2cm, and as can be seen in FIG. 2, the adhesive strength test values ​​after rolling from a measurement distance of 10 mm to 80 mm are approximately 137 to 382 gf / 2cm. It can be confirmed that the values ​​of the overall graph within the measurement distance are evenly distributed in a higher range compared to before rolling.

[0108] Example 2 is a binder structure incorporating phenoxybenzyl acrylate monomer, and the adhesive strength increased by 24% from 175 to 217 after rolling. As can be seen in FIG. 1, the adhesive strength test values ​​before rolling from a measurement distance of 10 mm to 80 mm are approximately 107 to 286 gf / 2cm, and as can be seen in FIG. 2, the adhesive strength test values ​​after rolling from a measurement distance of 10 mm to 80 mm are approximately 129 to 369 gf / 2cm, indicating that the values ​​of the overall graph within the measurement distance are evenly distributed in a higher range compared to before rolling.

[0109] Example 3 is a binder structure incorporating 2-phenyl-2-phenoxyethyl acrylate monomer, and the adhesive strength after rolling increased by 16% from 222 to 258. As can be seen in Fig. 1, the adhesive strength test values ​​before rolling from a measurement distance of 10 mm to 80 mm are approximately 155 to 296 gf / 2cm, and as can be seen in Fig. 2, the adhesive strength test values ​​after rolling from a measurement distance of 10 mm to 80 mm are approximately 180 to 403 gf / 2cm. It can be confirmed that the values ​​of the overall graph within the measurement distance are evenly distributed in a higher range compared to before rolling.

[0110] As such, experimental results in Examples 1 to 3 showed that the adhesive strength of the binder produced by the present invention increased by 10 to 30% after rolling.

[0111] Comparative Example 1 is a binder without added oil-soluble monomer, and the adhesive strength after rolling decreased by 54% from 185 to 85, showing the largest decrease in adhesive strength after rolling and the lowest adhesive strength value after rolling among the experimental examples. As can be seen in Fig. 1, the adhesive strength test values ​​before rolling from a measurement distance of 10 mm to 80 mm are approximately 114 to 266 gf / 2cm, and as can be seen in Fig. 2, the adhesive strength test values ​​after rolling from a measurement distance of 10 mm to 80 mm are approximately 63 to 100 gf / 2cm, indicating that the overall graph values ​​within the measurement distance are distributed as decreased compared to before rolling.

[0112] Comparative Example 2 is a binder structure incorporating a lauryl methacrylate monomer, which is a long-chain binder rather than an aromatic compound that is a lipophilic monomer. After rolling, the adhesive strength decreased by 36% from 147 to 94. As can be seen in Fig. 1, the adhesive strength test values ​​before rolling from a measurement distance of 10 mm to 80 mm are approximately 91 to 177 gf / 2cm, and as can be seen in Fig. 2, the adhesive strength test values ​​after rolling from a measurement distance of 10 mm to 80 mm are approximately 63 to 142 gf / 2cm, indicating that the overall graph values ​​within the measurement distance are distributed as decreased compared to before rolling.

[0113] Comparative Example 3 is a binder structure incorporating propylene glycol monomethacrylate monomer, which is a binder having a ring structure rather than an aromatic compound. After rolling, the adhesive strength decreased by 48% from 205 to 107. As can be seen in Fig. 1, the adhesive strength test values ​​before rolling from a measurement distance of 10 mm to 80 mm are approximately 144 to 268 gf / 2cm, and as can be seen in Fig. 2, the adhesive strength test values ​​after rolling from a measurement distance of 10 mm to 80 mm are approximately 70 to 191 gf / 2cm, indicating that the overall graph values ​​within the measurement distance are distributed as decreased compared to before rolling.

[0114] In the case of Comparative Examples 1 to 3, it can be confirmed that the adhesive strength decreased significantly by 30 to 60% after rolling.

[0115] The adhesive strength of Comparative Examples 1 to 3 before rolling is in the range of 100 to 250, indicating that the adhesive strength is relatively high. As such, the water-soluble binder structure is hard and has good adhesive strength, but as can be seen from the fact that the adhesive strength after rolling decreased significantly to the range of 50 to 150, it is not strong against rolling.

[0116] This property of being weak in rolling and breaking after rolling is primarily unsuitable for electrode formation, and if used as a binder for silicon anodes, it is not suitable for use because it cannot adapt to volume changes caused by the volume expansion of silicon anode materials.

[0117] In other words, as a result of comparing the adhesive strength after rolling through the examples and comparative examples, it was confirmed that while the adhesive strength increased by 10 to 30% in the examples after rolling, the adhesive strength actually decreased by 30 to 60% in the comparative examples. In light of these results, it was confirmed that the present invention can produce a binder with superior adhesive strength after rolling compared to the prior art using water-soluble binders such as Comparative Examples 1 to 3.

[0118] Meanwhile, when the adhesive strength was measured after rolling to 90% of the electrode thickness, the adhesive strength values ​​of Examples 1 to 3 ranged from 217 to 262 gf / 2cm, and it was confirmed that they showed much higher adhesive strength values ​​than the adhesive strength values ​​of Comparative Examples 1 to 3 before rolling (147 to 205 gf / 2cm, and after rolling 85 to 107 gf / 2cm).

[0119] As a result, it was confirmed that the adhesive strength after rolling of the binder incorporating a monomer containing an aromatic compound, as in Examples 1 to 3 of the present invention, exhibited much higher performance compared to the adhesive strength of Comparative Examples 1 to 3 using a monomer without an aromatic compound.

[0120] It is determined that the physical properties of the binder according to the present invention can be achieved because the structure of the aromatic compound included within the polymer structure imparts free volume to the binder and enhances impact resistance, so that the structure does not collapse even after rolling.

[0121] By comparing the adhesive strength values ​​after rolling in Examples 1 to 3 and Comparative Example 2, it can be confirmed that a binder structure containing a lipid-soluble monomer having an aromatic compound has strong characteristics for rolling, and exhibits a phenomenon where the adhesive strength does not decrease and increases even after rolling, whereas in a binder structure that does not use a lipid-soluble monomer having an aromatic compound, the adhesive strength after rolling decreases significantly.

[0122] Through the analysis of the embodiments and comparative examples of the present invention, it was confirmed that lipid-soluble monomers containing aromatic compounds help improve the rigid properties of water-soluble binders.

[0123] Reference Example 1 is a commercially available SBR (Manufacturer: Zeon) / CMC (Manufacturer: GLchem) binder, and the adhesive strength increased by 40% from 99 to 139 after rolling. That is, similar to the binders of Examples 1 to 3, Reference Example 1 showed a tendency for the adhesive strength to increase after rolling compared to before rolling; however, since the measured adhesive strength did not significantly reach that of Examples 1 to 3, it was confirmed that the adhesive strength of the binder according to the present invention exhibits superior performance. Although the commercially available SBR / CMC binder also contains aromatic compounds, it is in a water-dispersible form in which polymer particles are dispersed in a nano-form, whereas the binder of the present invention is a water-soluble binder in a solution form in which the polymer form is completely dissolved. This difference results in a difference in the adhesive strength of the binders.

Claims

Claim 1 A binder for an electrode of a secondary battery prepared by polymerizing a composition comprising at least two water-soluble monomers and at least one lipid-soluble monomer, wherein the composition is a compound satisfying the following chemical formula 1. The above polymerization is carried out by adding a lipid-soluble monomer to a water-soluble binder using an emulsifier and then synthesizing it through a chain reaction using an initiator. [Chemical Formula 1] As a binder for electrodes of a secondary battery, wherein k in Chemical Formula 1 ranges from 500 to 950, l ranges from 50 to 500, and m ranges from 1 to 200, M is one selected from alkali metals, alkaline earth metals, transition metals, and nitrogen compounds having a cation form, and R1 is a molecule having 1 to 5 benzene rings, The above binder is a water-soluble binder for electrodes of a secondary battery, provided in a solution form in which the polymer form is completely dissolved. Claim 2 In claim 1, the water-soluble monomer is an anionic unsaturated monomer and its salt, such as vinylpyrrolidone, silica, 4-vinylphenol, phosphoric acid, 4-vinylphenyl sulfate, maleic acid, diallyldimethylammonium chloride, (meth)acrylic acid, (anhydrous)maleic acid, itaconic acid, cinnamic acid, vinylsulfonic acid, allyltoluenesulfonic acid, vinyltoluenesulfonic acid, styrenesulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, 2-(meth)acryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, 2-hydroxyethyl methacrylic acid, 2-hydroxyethyl(meth)acryloylphosphate, 2-hydroxyethyl(meth)acryloylphosphate, 2-mercapto group-containing unsaturated monomer, phenolic hydroxyl group-containing unsaturated monomer; A binder for an electrode of a secondary battery comprising one or more selected from (meth)acrylamide, N-ethyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, etc., an amide group-containing unsaturated monomer; N,N-dimethylaminoethyl(meth)acrylate, N,N-dimethylaminopropyl(meth)acrylate, and N,N-dimethylaminopropyl(meth)acrylamide. Claim 3 In claim 1, the lipid-soluble monomer is an aromatic vinyl compound such as styrene, vinyltoluene, α-methylstyrene, divinylbenzene, etc.; Unsaturated carboxylic acid esters such as (meth)acrylate methyl, (meth)acrylate 2-hydroxyethyl, (meth)acrylate t-butyl, (meth)acrylate n-hexyl, (meth)acrylate isobutyl, (meth)acrylate cyclohexyl, (meth)acrylate 2-ethylhexyl, (meth)acrylate lauryl, (meth)acrylate stearyl, (meth)acrylate benzyl, mono or di(meth)acrylate of (poly)ethylene glycol, mono or di(meth)acrylate of (poly)propyl glycol, mono- or di-(meth)acrylate of 1,4-butanediol, mono-, di- or tri-(meth)acrylate of trimethylolpropane, allyl compounds such as diallyl phthalate, diallylacrylamide, trialyl(iso)cyanurate, and trialyl trimellitate, A binder for electrodes of a secondary battery comprising one or more selected from (poly)oxyalkylene glycol di(meth)acrylates such as (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, butadiene, isoprene, and chloroprene. Claim 4 A binder for an electrode of a secondary battery according to claim 1, wherein M in Chemical Formula 1 comprises one or more selected from lithium, sodium, potassium, rubidium, magnesium, calcium, barium, titanium, zirconium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, manganese, iron, cobalt, nickel, palladium, platinum, copper, silver, gold, zinc, cadmium, mercury, and ammonium ions. Claim 5 A binder for an electrode of a secondary battery comprising one or more selected from the group consisting of: persulfates such as benzoin derivatives, benzyl derivatives, acetophenone derivatives, benzophenone derivatives, sodium persulfate, potassium persulfate, and ammonium persulfate; and compounds comprising a reducing compound such as L-ascorbic acid or sodium bisulfite in combination with a persulfate or peroxide, wherein the initiator used in preparing the binder of Formula 1 is a persulfate of a benzoin derivative, benzyl derivative, acetophenone derivative, benzophenone derivative, sodium persulfate, etc.; hydrogen peroxide, t-butyl peroxide, methyl ethyl ketone peroxide, 2,2'-azobis(2-amidinopropane)dihydrochloride, 2,2'-azobis[2-(2-imidazoline-2-yl)propane]dihydrochloride, or a compound comprising a persulfate or peroxide. Claim 6 In claim 1, the emulsifier used in preparing the binder of Formula 1 comprises one or more selected from polyoxyalkylenealkylphenyl ether, polyoxyalkylenealkyl ether, alkyl polyglucoside, polyglycerin alkyl ether, polyglycerin fatty acid ester, polyoxyalkylene fatty acid ester, sorbitan fatty acid ester, fatty acid soap, rosin soap, alkyl sulfonate, alkylaryl sulfonate, alkyl sulfosuccinate, polyoxyethylene alkyl sulfate, polyoxyethylenearyl sulfate, stearyl trimethylammonium, cetyl trimethylammonium, and lauryl trimethylammonium, for use as an electrode binder for a secondary battery. Claim 7 A binder for an electrode of a secondary battery according to claim 1, wherein the molecular weight (Mw) of the binder of Chemical Formula 1 is 200,000 to 2,000,000.

Citation Information

Patent Citations

  • Binder for secondary battery exhibiting excellent adhesive force

    KR1020110098111A

  • Binder aqueous solution for electrode of lithium ion battery, slurry for negative electrode of lithium ion battery, negative electrode for lithium ion battery and lithium ion battery

    KR102301237B1